UNIVERSAL LEARNING ACTIONS OF PRIMARY SCHOOL STUDENTS: ESSENCE, CONTENT AND THEORETICAL FOUNDATIONS - Orif Abdukhalikovich Ganiyev (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
Abstract: This article analyzes the essence, content, and theoretical foundations of universal learning actions in primary school students from a scientific and pedagogical point of view, highlighting their role in the development of students' cognitive activity, independent thinking, and activity in the educational process through personal, regulatory, cognitive, and communicative types, as well as the theoretical aspects of modern pedagogical approaches to their formation.